Production of medium-chain volatile flavour esters in Pichia pastoris whole-cell biocatalysts with extracellular expression of Saccharomyces cerevisiae acyl-CoA:ethanol O-acyltransferase Eht1 or Eeb1 - Zhuang, Shiwen; Fu, Junshu; Powell, Chris; Huang, Jinhai; Xia, Yihe; Yan, Ruixiang (SpringerOpen, 2015)
Medium-chain volatile flavour esters are important molecules since they have extensive applications in food, fragrance, cosmetic, paint and coating industries, which determine different characteristics of aroma or taste in commercial products. Biosynthesis of these compounds by alcoholysis is catalyzed by acyl-CoA:ethanol O-acyltransferases Eht1 or Eeb1 in Saccharomyces cerevisiae. In this study, these two yeast enzymes were selected to explore their preparations as the form of whole cell biocatalysts for the production of volatile flavour esters. Here, the novel whole cell biocatalysts Pichia pastoris yeasts with functional extracellular expression of Eht1 or Eeb1 were constructed. Flavour production was established through an integrated process with coupled enzyme formation and ester biosynthesis in the recombinant yeasts in one pot, leading to the formation of volatile C6–C14 methyl and ethyl esters from wort medium. Interestingly, there is no significant difference between P. pastoris-EHT1 and P. pastoris-EEB1 in substrate preference during flavour biosynthesis, indicating a similar role of Eht1 and Eeb1 in P. pastoris cells, in contradiction with previous findings in S. cerevisiae to some extent. Consequently the study not only provides a greater understanding of these two enzymes in a heterogeneous host, but also demonstrated the positive effect of the recombinant Eht1 and Eeb1 in ester formation by P. pastoris live cells, potentially paving the way towards achieving efficient production of volatile flavour by an integrated biocatalytic system composed of recombinant enzyme production and flavour biosynthesis.